Propranolol reverses open field effects on frustration - Justel, Nadia (2014)
Reactivity to a reward is affected by prior experience with different reinforcer values of that reward, a phenomenon known as incentive relativity. Incentive relativity can be studied via the consummatory successive negative contrast (cSNC) paradigm, in which acceptance of 4% sucrose is assessed in animals that had been exposed to 32% sucrose. These downshifted animals usually exhibit significantly less sucrose acceptance than animals that always received the 4% sucrose solution. In previous work, we found that exploration of a novel open field (OF) before the first trial with the downshifted solution attenuated the contrast effect. The goal of the present experiments was to expand the knowledge on the effects of OF exposure on cSNC. We evaluated the effect OF exposure before the second downshift trial and assessed the mediational role of the adrenergic system in the effects of OF during the first and second trial of cSNC. The results indicate that OF applied before the first or second downshift trials exert opposite effects and that the adrenergic system is involved in the acquisition and consolidation of the OF information.